Geochemical characteristics and evolution process for hot spring gas of the north-south graben system in Qinghai−Xizang Plateau - Sanyu QUAN; Yingchun WANG; Xin TANG; Jinlin ZHOU; Lu LUO; Rongcai SONG (Shuiwen dizhi gongcheng dizhi)
While the hydrogeochemical characteristics of a single geothermal field in Qinghai−Xizang Plateau are well understood, the study of hot spring gases in various graben systems and their spatial characteristics and evolutionary processes, remains insufficiently explored. The study reported 16 hot spring gases from three grabens (Cuona−Woka garben, Yadong−Gulu garben and Shenzha−Dingjie garben) in Qinghai−Xizang Plateau. The composition and isotopic characteristics as well as the sources of hot spring gas were analyzed. Additionally, the relationship between the content of hot spring gas and the reservior temperature was conducted in the three garbens. Three types of gases were distinguished in Qinghai−Xizang Plateau by using the “mantle suture line” as the boundary. The results show that hot spring gases in the north and south sides of the boundary have undergone different evolutionary processes, with some samples in the south showing evidence of degassing and fractionation. The sources of helium and carbon isotopes in the hot spring gases are mainly derived from the crust, and the migration of helium is dependent on the flow of carbon dioxide. There are significant differences of reservior temperature in the three garbens, with a higher temperature (225 °C) in the Yadong−Gulu graben. This study provides insights in understanding the relationship between structures, hot spring gases, and geothermal fields in Qinghai−Xizang Plateau. The exploration of gas geochemical characteristics and their evolutionary processes are significant for the understanding of the underground geological processes and the exploitation and utilization of geothermal resources.